Description of two new species of Walkerella (Pteromalidae, Otitesellinae) from China with a key to species of the genus - Ma, Yun-Cui; Peng, Yan-Qiong; Yang, Da-Rong (Zootaxa, 2013)
Walkerella is an Old World genus of non-pollinating fig wasps in the subfamily Otitesellinae (Chalcidoidea, Pteromalidae). It is the most widely distributed genus of the subfamily, though there has been only six known world species. This paper describes two new species associated with the host Ficus subsection Conosycea of section Urostigma, subgenus Urostigma in Xishuangbanna, China. The two new species, Walkerella nigrabdomina Ma & Yang sp. nov. and W. curtipedis Ma & Yang sp. nov., are described from specimens reared from Ficus pisocarpa and Ficus curtipes, respectively. A key to all described species of Walkerella found is provided.